Pelatihan Pemasaran Produk Dengan Pemanfaatan Teknologi Informasi Secara Online - Budiharjo, Roy; Mahrani, Suri (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2020)
The purpose of this community service is to provide understanding to participants, especially MSMEs, on how to market products online by utilizing technology for free. This training will introduce the products offered in the long term compared to conventional means that can offer in the short term. This training is given to people in South Meruya village who want to become entrepreneurs through the use of technology to improve product marketing efficiency. The results of this training can be used to increase competitiveness and public knowledge about marketing in today's digital era. Keywords: online marketing, MSME's